Fuzzy Systems & Operations Research and Management - Cao, Bing-Yuan; Liu, Zeng-Liang; Zhong, Yu-Bin; Mi, Hong-Hai (Advances in Intelligent Systems and Computing, 2016)
This book includes results of the seventh International Conference on Fuzzy Information and Engineering (ICFIE'2014) and the 1st International Conference of Operations Research and Management (ICORM'2014) on November 7-11, 2014 in ZhuHai, China. The book, contains 35 selected high-quality papers, and is divided into five main parts: Part I focuses on ``Fuzzy Systems and Its Applications", Part II on ``Fuzzy Mathematics and Its Applications", Part III discusses ``Fuzzy Information and Computer", Part IV is devoted to ``Operations Research and Management and Its Applications" and Part V includes various other topics.  .